High Fructose Intake During Pregnancy in Rats Influences the Maternal Microbiome and Gut Development in the Offspring - Astbury, Stuart; Song, Aleida; Zhou, Mi; Nielsen, Brent; Hoedl, Abha; Willing, Benjamin P.; Symonds, Michael E.; Bell, Rhonda C. (Frontiers in Genetics, 2018)
Studies in pregnant women indicate the maternal microbiome changes during pregnancy so as to benefit the mother and fetus. In contrast, disruption of the maternal microbiota around birth can compromise normal bacterial colonisation of the infant’s gastrointestinal tract. This may then inhibit development of the gut so as to increase susceptibility to inflammation and reduce barrier function. The impact of modulating fructose intake on the maternal microbiome through pregnancy is unknown, therefore we examined the effect of fructose supplementation on the microbiome together with the immediate and next generation effects in the offspring. Wistar rat dams were divided into control and fructose fed groups that received 10% fructose in their drinking water from 8 weeks of age and throughout pregnancy (10-13 weeks). Maternal fecal and blood samples were collected pre-mating (9 weeks) and during early (gestational day 4-7) and late pregnancy (gestational day 19-21).We show supplementation of the maternal diet with fructose modulated the maternal microbiome, increased diversity and abundance of Lactobacillus and Bacteroides species. In offspring maintained on this diet up to pregnancy and term there was a reduction in gene expression of markers of gut barrier function that could adversely affect its function. This was associated with an exacerbated insulin response to pregnancy, reduced birth weight, but increased fat mass. In conclusion dietary supplementation with fructose modulates the maternal microbiome in ways that could adversely affect fetal growth and later gut development.